Pengaruh Inovasi Produk, Promosi dan Harga Terhadap Kepuasan Pelanggan Abqkebab Surabaya - Loqman Ananta Azaria; Rusdi Hidayat Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The main issue in this study is examining how product innovation, promotion, and pricing influence customer satisfaction at Abkebab Surabaya. The research sample consists of 131 participants who are Abkebab visitors. This study employs quantitative techniques and secondary data obtained from various sources such as books, journals, and other documents related to the subject matter, specifically the impact of product innovation, promotion, and pricing on customer satisfaction at Abkebab Surabaya. The data analysis methods include descriptive analysis, instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing, partial and simultaneous tests. The data processing tool used is SPSS version 26. The results of the study indicate a positive and significant partial influence of both product innovation and promotion, as well as pricing, on customer satisfaction. There is also a combined influence of product innovation, promotion, and pricing on customer satisfaction.